Planificación de un sistema de gestión integrado para una organización de investigación agropecuaria (2019)
This research paper shows the approach to structure a quality management and integrated environmental management system under the technical standards ISO 9001:2015 and ISO 14001:2015, in a public agricultural research organization that produces seeds and studies to contribute to Ecuador’s food safety. The importance of the research lies in the social impact that the organization has on the production of seeds, which will become food for the population. Through the structuring of an integrated management system, the image will be consolidated before the interested parties, generating confidence and guaranteeing that the products and services they deliver comply with international standards of environmental and quality management. To achieve the structuring of the Integrated Management System (SGI), an individual analysis of the environmental management and quality management models is conducted to find convergences enabling the proposal of an integrated management model, under the requirements of technical standards ISO 9001:2015 and ISO 14001:2015. Then, a situational diagnosis is made to the organization, to determine the current status regarding quality and environmental management, in accordance with the requirements established by the technical standards ISO 9001:2015 and ISO 14001:2015, becoming a starting point for structuring the system and its subsequent implementation. As a result, an integrated management system with four phases that must be applied sequentially, is obtained. Two phases were applied in the present research study.